Cumulative Dose of Prostaglandin E1 Determines Gastrointestinal Adverse Effects in Term and Near-Term Neonates Awaiting Cardiac Surgery: A Retrospective Cohort Study - Noa Ofek Shlomai; Gilad Lazarovitz; Benjamin Koplewitz; Smadar Eventov Friedman (MDPI AG, 2023)
Objective: This study aimed to assess the association between treatment characteristics of prostaglandin E1 including initiation time and duration, maximal and cumulative doses, and adverse effects. Design: A retrospective cohort study in which medical records of neonates with duct-dependent lesions were studied for treatment parameters and adverse effects. Multivariable logistic regression model was applied for testing the effect PGE1 variables on outcomes. Main outcome measures: The primary outcomes of this study were association of adverse effects of PGE1 treatment with maximal dose, cumulative dose, and treatment duration. The secondary outcomes included safety of feeding in infants treated with PGE1. Results: Eighty-two infants with duct-dependent lesions receiving PGE1 were included. Several infants who received early PGE1 treatment required ventilation support. Feeds were ceased more often as the cumulative dose and duration of PGE1 treatment increased. Gastrointestinal adverse effects were significantly associated with the cumulative dose of PGE1 and treatment duration. Apneas, hyperthermia, and tachycardia were associated with maximal dose. Our data did not demonstrate a difference in the incidence of NEC associated with characteristics of PGE1 treatment. Conclusion: Cumulative PGE1 dose is associated with gastrointestinal adverse effects in neonates. Lower doses should be considered in neonates expecting prolonged PGE1 treatment.